2020
DOI: 10.3389/fpsyg.2020.01582
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths: Person–Environment Fit and Relationships With Job and Life Satisfaction

Abstract: Several studies demonstrated the relevance of character strengths in the workplace. For example, it has been shown that they positively relate to performance and are strong predictors of job satisfaction. Furthermore, it was demonstrated that occupational groups differ in their average levels of character strengths. However, little is known about the effects of the congruence between a person's strengths profile with the average profile within an occupational group (environmental congruence) on well-being. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
(73 reference statements)
0
25
0
3
Order By: Relevance
“…Qual. Life 15, 307-328. doi: 10.1007/s11482-018-9695-z Wagner, L., Holenstein, M., Wepf, H., and Ruch, W. (2020b). Character strengths are related to students' achievement, flow experiences, and enjoyment in teacher-centered learning, individual, and group work beyond cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Qual. Life 15, 307-328. doi: 10.1007/s11482-018-9695-z Wagner, L., Holenstein, M., Wepf, H., and Ruch, W. (2020b). Character strengths are related to students' achievement, flow experiences, and enjoyment in teacher-centered learning, individual, and group work beyond cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…While the character strengths associated most strongly with job satisfaction overlap with those most strongly associated with life satisfaction (i.e., zest, hope, curiosity, love, and gratitude), differential relationships were also found for different occupational subgroups (Peterson et al, 2010;Heintz and Ruch, 2020). Gander et al (2020b) recently showed in a sample that was nationally representative for Switzerland that work satisfaction is not only concurrently but also predictively related to character strengths (i.e., zest, love, kindness, social intelligence, leadership, forgiveness, gratitude, and hope showed positive relationships at all time points). Underlining the role of the work context, a fit with the typical character strengths' configuration in the occupational group is also relevant for job satisfaction (Peterson et al, 2010;Gander et al, 2020b).…”
Section: Workmentioning
confidence: 96%
See 1 more Smart Citation
“…The present study had six main aims: first, we aimed at examining the relationships between current and ideal team roles and character strengths with work-related outcomes. Thereby, we intended to corroborate earlier findings on positive relationships of team roles (Gander et al, 2018;Ruch et al, 2018) and character strengths (e.g., Harzer and Ruch, 2014;Gander et al, 2020;Heintz and Ruch, 2020;Huber et al, 2020) with work-related outcomes and extending these findings by analyzing hitherto not studied outcomes, such as team performance and teamwork quality, and by additionally considering the team-level perspective. In line with previous findings, we expected positive relationships of all current team roles with work satisfaction, teamwork quality, and performance because enactment of these roles is considered conducive to achieving work tasks as well as to being satisfied with one's work.…”
Section: The Present Studymentioning
confidence: 67%
“…Previous researches on life satisfaction can also be classified into two categories according to its' focusses, which are specific domains of life include, for instance, research on marriage and subjective well-being [11, 12,13]; Job satisfaction and life satisfaction [14,15,16] and research on health and subjective well-being [17,18,19]. Thus, the focus on research on life satisfaction can be subjective as well as objective too.…”
Section: Streams Of Research On Life Satisfactionmentioning
confidence: 99%